À propos de quelques décalages de l’historiographie de l’anarchisme espagnol - Michel Ralle (Cahiers de Civilisation Espagnole Contemporaine)
Spanish anarchism studies have been impacted in more ways than one since they gained access to university departments in the early 60’s. Political history did shed light on the ideological debates and inner tensions. But attempts to work out the relationship between the libertarian strand and the way the various components of Spanish society evolved, have often overlooked the ways it merged in society, even as the discipline focused on the relationship between social and imagined experiments. This makes even more evident how Jacques Maurice lives up to the demanding standards he set for himself from the outset. These standards implied an extremely meticulous, constantly updated knowledge of social conditions in lower class and proletarian milieux, – and not only in the Andalusian countryside, as well as a critical approach (including political and cultural references), to the historiography of Spain’s anarchism. This is a decisive contribution to a good many of its more significant items.